PENGADAAN TAMAN BACA MASYARAKAT SEBAGAI SOLUSI DALAM MENINGKATKAN MINAT BACA MASYARAKAT DESA CIBENING - Mursyidah, Azizah; Rinawati; Susilawati, Ucu; Isfani, Rizka; Munir, M.Misbahul (Sahid Mengabdi: Jurnal Pengabdian Masyarakat Institut Agama Islam Sahid Bogor, 2023)
The unavailability of reading facilities and the large number of teenagers who drop out of school are a problem in Cibening Village resulting in low interest in reading in the community. The purpose of research and implementation of Community Reading Gardens is to increase public interest in reading. The method used in this study is a qualitative descriptive method with data collection techniques interview, observation, and documentation as well as using data analysis techniques, namely triangulation. The implementation of the Procurement of Community Reading Parks is by making village libraries or Community Reading Parks through several stages, namely the preparation stage, the implementation stage, as well as the evaluation and follow-up stages.